KONFLIK PERSONALITAS TOKOH UTAMA DALAM NOVEL AL- LISHU WAL KILAB KARYA NAGUIB MAHFOUZ (Kajian Psikologi Sastra Sigmund Freud) - Gina Nurhikmah; Fadlil Yani Ainusyamsi; Dedi Supriadi (Hijai - Journal on Arabic Language and Literature, 2026)
Humans essentially possess a personal life that involves inner conflicts within themselves. A person’s attitudes and actions are the result of the psychological struggles that occur within their mind. This is reflected in the character of Said Mahran, the protagonist in Al-Liṣṣ wa al-Kilāb (The Thief and the Dogs) by Naguib Mahfouz. This study aims to examine the personality structure of the main character and to identify the internal and external factors underlying his personality conflict in the novel. The research found the presence of the elements of the Id, Ego, and Superego, which contribute to the protagonist’s personality conflict in The Thief and the Dogs. The personality structure consisting of the Id, Ego, and Superego forms an individual’s personality and determines the attitudes and actions taken by that individual. Keywords: Personality Psychology, Literature, Main Character.